Caring for the community affected by the Covid-19 pandemic in Mataram Sei Putih Village, Riau - Vincent Natanael Hasibuan; Ari Rahman; Mega Mutiara Sari; Fatimah Dinan Qonitan; Nova Ulhasanah; Ariyanti Sarwono; Evi Siti Sofiyah; Nurulbaiti Listyendah Zahra; Betanti Ridhosari; I Wayan Koko Suryawan (Community Empowerment, 2021)
The Covid-19 pandemic has a direct impact on public health and indirectly on the environment and the community's economy. One of the areas that has had the greatest impact is Sei Putih, Riau. The occurrence of massive layoffs caused the ability of the community to purchase food needs to be quite low. The purpose of this activity is to provide socialization of health protocols and the provision of basic necessities to the needs. The socialization of health protocols was carried out so that during the distribution of groceries there would not be a crowded crowd. During the socialization, people are also required to wear masks and wash their hands. The food items were given on April 4, 2021. The basic food items were 5 kg of rice, 1 L of cooking oil, 1 can of sardines, 2 packs of Indomie, and 500 grams of sugar. From the range of 1-5, the assessment of program is 4.65 and satisfaction is 4.8. This shows that the activity is very good to be carried out to foster awareness in the community.